The Important Development of Executing of ‘Waqf Irsod’ in Contemporary Malaysia - Bhari, A.; Rani, M.A.M.; Rahman, Azhar Abdul; Radzi, N.A.M.; Abdullah, L.; Rosele, M.I.; Sayin, B.; Hamid, M.H.A. (American Scientific Publishers, 2016)
The study aims to investigate the significance of the executing of ‘waqf irsod’ in Malaysia. In general, the implementation of ‘waqf irsod’ occurs when the ‘Baitulmal’ or local authority donates for the construction of important infrastructures for the benefit of Muslims. The issue here is, on the slow progress of ‘waqf irsod’ practiced in Malaysia although its importance is in immediate need to the context of thinking development and infrastructure of the contemporary Islamic societies. A qualitative study using library research methods in collecting relevant data. The data were generated through the inductive, deductive and comparative methods. The study found that ‘waqf irsod’ plays a big role in sustaining the development of Muslims in Malaysia in view of the current market’s price of lands is too expensive. Therefore, the authorities and non-governmental organizations must work closely to deliver the system to promote the implementation of the ‘waqf irsod.’